Theoretical Apparitions of Haiku : An Intermedial Interrogation of Modernity - Nelson, Tollof (Cinémas)

(untitled) (Cinémas, 2000)
ABSTRACTAt the turn of the twentieth century, the translation and the reception of haiku poetry allowed for theoretical advances beyond the purview of the literary. The haiku-idiom reinvented itself as a practice of poetry as audio-visual technique : haiku as a line of flight, medium of another relationship to language and to images. A hybrid-model of the modernist arts (poetry photography, film), the haiku-idiom became a vehicle for theories articulating the experience of a new spatio-temporal economy of images. As a mode of writing in laconic fragments, gestures of everyday-life, and shadows of memory, the haiku-idiom mobilized for others a relationship of movement, opacity, and distance to language.